2014
DOI: 10.1039/c3ra45429k
|View full text |Cite
|
Sign up to set email alerts
|

Activity enhancement of G-quadruplex/hemin DNAzyme by spermine

Abstract: Biogenic polyamines participate in regulating gene expression, activating DNA synthesis and facilitating DNA-protein interaction through interaction with DNA/RNA. The interaction of polyamines with G-quadruplexes (G4s) has been reported to modulate the structure of G4s. In this paper, we investigate the effects of polyamines on one of the properties of G4s, G4/hemin peroxidase. Three polyamines (spermine, spermidine and putrescine) are found to have positive effects on different G4/hemin DNAzymes, in which spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 50 publications
2
51
1
Order By: Relevance
“…The obtained results showed that the activity of PMDNAzyme prepared with EAD2 aptamer was practically twice those of PMDNAzymes constructed with PS2.M and [B7]-3-0 aptamers (data not shown). High catalytic activity of PMDNAzyme with EAD2 was also reported previously [30,34]. Therefore, further work was carried out using the hemin-EAD2 complex as PMDNAzyme.…”
Section: Resultsmentioning
confidence: 62%
“…The obtained results showed that the activity of PMDNAzyme prepared with EAD2 aptamer was practically twice those of PMDNAzymes constructed with PS2.M and [B7]-3-0 aptamers (data not shown). High catalytic activity of PMDNAzyme with EAD2 was also reported previously [30,34]. Therefore, further work was carried out using the hemin-EAD2 complex as PMDNAzyme.…”
Section: Resultsmentioning
confidence: 62%
“…In a recent study by Qi et al., changes in DNAzyme structure and its activity by spermine were evaluated. CD and UV/Vis spectral analysis showed that this polyamine improved the catalytic reaction of DNAzyme .…”
Section: Discussionmentioning
confidence: 94%
“…G-quadruplex/hemin complexesc an catalyze the oxidation of substrates (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonica cid) (ABTS),3 ,3',5,5'-tetramethylbenzidine (TMB), or luminol) in the presence of H 2 O 2 ,a nd the subsequentc olor change (ABTS, l max = 415 nm when oxidized) has been used in colorimetric and/or chemiluminescent detection of various targets.C ompared with proteinous enzymes, G-quadruplex/hemin DNAzymes have many advantages. Smallm olecule additives (ATP or spermine), [13][14][15] may be added to the G-quadruplex/hemin system;a lternatively, covalent conjugation of ac ationicp eptide [16] or hemin to G-quadruplex, [17] or chemical modification of G-quadruplexes [18] have been used. Furthermore, it is asimple and sensitive biosensor and molecular machine that is suitable for the detection of multiple targets such as metal ions, [3] small molecules, [4] and biomolecules (DNA and proteins), [5,6] which were described in recent reviews.…”
Section: Introductionmentioning
confidence: 99%